Pengembangan Electronic-Public Relation Melalui “MP Mobile Apps” untuk Optimalisasi Sistem Informasi - Aditya Chandra Setiawan; Mohammad Syahidul Haq; Ellena Ihza Katerina; Satria Adi Wisesa (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstract: The purpose of this study is to optimize information services for residents of the Department of Education Management and the general public related to improving the quality of information services in a practical and integrated manner. The method in this study uses the Waterfall Model, which is 5 stages (Analysis, Design, Implementation, Testing, Maintenance). The results of the research obtained products that have been in accordance with the design process following the Waterfall Model, in the form of the 'MP Mobile Apps' application starting from features to the process of filling in information on the application by adjusting the conditions and development of programs or activities organized by the Department of Education Management, so that the optimization of the information system through the E-PR concept is realized and has been used by residents of the Department of Education Management. Keywords: Development, Electronic Public Relations, Optimization, Management Information System Abstrak: Tujuan penelitian ini yaitu optimalisasi layanan informasi bagi warga Jurusan Manajemen Pendidikan dan masyarakat umum terkait meningkatkan kualitas layanan informasi secara praktis dan terintegrasi. Metode dalam penelitian ini menggunakan Waterfall Model, yaitu ada 5 tahapan (Analysis, Design, Implementation, Testing, Maintenance). Hasil penelitian diperoleh produk yang telah sesuai proses perancangan mengikuti Waterfall Model, berupa aplikasi ‘MP Mobile Apps’ mulai dari fitur hingga proses pengisian informasi pada aplikasi dengan menyesuaikan kondisi dan perkembangan program atau kegiatan yang diselenggarakan Jurusan Manajemen Pendidikan, sehingga optimalisasi sistem informasi melalui konsep E-PR terwujud dan telah digunakan  oleh warga Jurusan Manajemen Pendidikan. Kata Kunci: Pengembangan, Electronic Public Relation, Optimalisasi, Sistem Informasi Manajemen